2013
DOI: 10.1080/ac.68.6.8000008
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise heart rate variability recovery: a time-frequency analysis

Abstract: These results indicate that exercise training exerts beneficial effects on post-exercise cardiac autonomic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…For the analyses of HRV, HRR and ΔHRR, we used data collected in post-warm-up recovery as these data allow analyses to be performed after standardised moderate-intensity exercise, similar to the procedures used by other authors [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the analyses of HRV, HRR and ΔHRR, we used data collected in post-warm-up recovery as these data allow analyses to be performed after standardised moderate-intensity exercise, similar to the procedures used by other authors [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the frequency domain the low-frequency spectral component (LF – frequency between 0.04 and 0.15 Hz) is considered an index that evaluates sympathetic and parasympathetic behavior [22, 23], while the high-frequency spectral component (HF – frequency between 0.15 and 0.4 Hz) is a marker of vagal modulation [22, 23]. The spectral analysis will be calculated from a tachograph using the fast Fourier transform algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Peçanha et al, 3 although they compared levels of physical activity among healthy individuals, the authors focused their analyses on the post-training period and also confirmed the increase in HRV in trained individuals. The authors described the need for more studies to confirm the potential cardioprotective effect of physical training on the cardiovascular system in clinical populations through a longitudinal design.…”
Section: Discussionmentioning
confidence: 93%